PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PULP MAKING 8 PT. INDAH KIAT PULP AND PAPER PERAWANG - Mikha Etalia; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aimed to determine the effect of education and training to employee performance in pulp production Pulp Making PT.Indah Kiat Pulp and Paper. Education and training as an independent variable (X) has been formulated by ability and skill instructors coach, the determination of material, facilities and infrastructure. While employee performance as the dependent variable (Y). This research was conducted on all employees pulp production Pulp Making PT.Indah Kiat Pulp and Paper by 40 people. Data obtained from the questionnaire and further processed and then tested using statistical analysis such as a simple linear regression analysis, test, and correlation analysis and determiniasi using SPSS17. The results showed that the test results of hypothesis testing tcount 6,513> ttable 2,024. This suggests that the education and training having an effect the level of employee performance. The magnitude of the education and training on employee performance in pulp production Pulp Making PT.Indah Kiat Pulp and Paper amounted to 52,8%.Keyword : education and training, employee performance, Pulp Making 8